Human security studies : theories, methods and themes - Peou, Sorpon (Singapore World Scientific, 2014)
Human Security Studies: Theories, Methods and Themes examines the concept of human security from different theoretical and methodological perspectives and shows how they help shed light on the different themes of global intervention. Liberal perspectives, represented by global legalism and developmentalism, share the optimism that human security can be ensured and enhanced through strengthening global governance. Realists remain skeptical about this liberal vision. While also critical of the liberal promise, critical theorists and feminists offer radical perspectives on human security. All these perspectives help explain the challenges of military intervention for human protection, micro-disarmament, international criminal justice, smart sanctions, human rights and democracy promotion, and human development.
Includes bibliographical references and index.
Keywords: Tham khảo